Fatores sócio-familiares associados ao reconhecimento de expressões faciais das emoções em idosos - Ianagui, Camila Corrêa (Universidade Federal de São Carlos, 2021)
Facial expressions are an important source of communication, both for transmission and recognition of the emotional state of the person who communicates. Demographic factors such as gender, age, and education may be related to performance on tasks of recognition of facial expressions of emotions (REFE). Few studies analyze the relationship between REFE and socio-family support in the elderly. Therefore, the study aims to verify if there is a relationship between social and family support with the recognition of facial expressions of emotions in participants of a community center for the elderly. This is a cross-sectional, observational, and descriptive study, carried out in a Community Center for the elderly in a city in the State of São Paulo. Those who did not understand the proposed assessments or who had cognitive impairment or severe depressive symptoms were excluded from the research. The study sample consisted of 30 volunteers, 4 men, and 26 women, with an average age of 69 years. Questionnaires were used to assess the socio demographic situation of the participants, family functionality through the “Family APGAR”, social support through the Medical Outcomes Study (MOS); and the instrument to assess the ability to recognize facial expressions of emotions “Penn Emotion Recognition Test”. Questionnaire performance was correlated with performance on the REFE task using Spearman correlation. It was observed that increased education is related to better performance in recognizing the emotion sadness (p = 0.027). The scores obtained in the Apgar Family Test and the Material Support domain of the MOS test had a negative and statistically significant correlation with the emotion fear (r = -0.586 and p = 0.001; r = -0.541 p = 0.002, respectively). In the Affective domain, also of the MOS test, a statistically significant positive correlation was observed (r = 0.379 and p = 0.042) with the neutral emotion in the REFE task. It was concluded that social support, more specifically material support, and family functionality influence the facial recognition of the expression of fear in the elderly.
Socio-family factors associated with the recognition of facial expressions of emotions in elderly
Keywords: Envelhecimento; Reconhecimento facial; Expressão facial; Emoções; Apoio social; Aging; Facial recognition; Facial expression; Emotions; Social support; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL